Global politics - Heywood, Andrew (Houndmills, Basingstoke Hampshire ; New York : Palgrave Macmillan, 2011)
"This book is a major new introduction to international relations/global politics. Written by a leading textbook author, it is engaging, stimulating and forward-looking, covering all the topics and theory students require at an introductory level"--
Includes bibliographical references p. 524-540 and index.
Keywords: International relations; World politics; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / Government / General; POLITICAL SCIENCE / Globalization